Peningkatan Kualitas Pembelajaran Sebagai Wujud Transformasi Pendidikan - F Ribudiyanti; Endah Reknaningsih; Nurkolis - (Universitas Negeri Malang, 2020)
Abstract: Educational transformation is a demand of the times that must be responded to with concrete steps in educational units, particularly in the implementation of the Independent Curriculum. This article describes the strategic efforts undertaken by the Principal of SMP Negeri 3 Satu Atap Kedungjati since the beginning of his leadership in 2023 to improve the quality of learning. Based on the 2022 Education Report Card data showing low achievements in literacy, numeracy, student character, and learning quality, the Principal conducted a reflection with teachers, identified challenges, and developed an improvement strategy focused on strengthening teacher competency as the primary implementers of the Independent Curriculum. This study used a qualitative descriptive method in accordance with the research process, starting with supervision, interviews, and collecting necessary documentation. The Principal took on the role of an agent of change through training, mentoring, and teacher empowerment. The results of this study serve as a foundation for realizing more meaningful, student-centered learning, and oriented towards the Pancasila Student Profile, given the school's remote geographical location and limited human resources and facilities. This change focuses on shifting from simply delivering material to developing student competency and character. Principals and teachers play a crucial role in building an innovative and responsive learning ecosystem. With the support of progressive policies and collaboration from all parties, educational transformation can be realized. SMP Negeri 3 Satu Atap Kedungjati remains committed to providing the best educational services, with a spirit of inclusive and sustainable change. This effort is reflected in the positive achievements of the 2025 Education Report, as concrete evidence that quality education can be achieved through hard work, collaboration, and a focus on student needs, skills training for teachers, a culture of reflection and collaboration, designing targeted quality improvement programs, and prioritizing transformative leadership. Keywords: Educational transformation; Merdeka Curriculum; learning quality; school principal; teacher competence Abstrak: Transformasi pendidikan merupakan tuntutan zaman yang harus direspon dengan langkah nyata di satuan pendidikan, khususnya dalam penerapan Kurikulum Merdeka. Artikel ini mendeskripsikan upaya strategis yang dilakukan Kepala SMP Negeri 3 Satu Atap Kedungjati sejak awal kepemimpinannya pada tahun 2023 untuk meningkatkan kualitas pembelajaran. Berdasarkan data Rapor Pendidikan tahun 2022 yang menunjukkan rendahnya capaian dalam literasi, numerasi, karakter murid, dan kualitas pembelajaran, Kepala sekolah melakukan refleksi bersama guru, memetakan tantangan, dan menyusun strategi perbaikan yang terfokus pada penguatan kompetensi guru sebagai pelaksana utama Kurikulum Merdeka. Adapun penelitian ini menggunakan metode kualitatif deskriftif sesuai pada jalannya penelitian mulai pada ovserbasi, wawancara dan pengambilan dokumentasi yang diperlukan. Kepala sekolah mengambil peran sebagai agen perubahan melalui pelatihan, pendampingan, dan pemberdayaan guru. Hasil dari penelitian ini menjadi fondasi dalam mewujudkan pembelajaran yang lebih bermakna, berpusat pada peserta didik, dan berorientasi pada Profil Pelajar Pancasila terdasarkan letak geografis sekolah yang terpencil serta keterbatasan SDM dan sarana. Perubahan ini fokus dari sekadar penyampaian materi menuju pengembangan kompetensi dan karakter siswa. Kepala sekolah dan guru memainkan peran penting dalam membangun ekosistem pembelajaran yang inovatif dan responsif. Dengan dukungan kebijakan yang progresif serta kolaborasi semua pihak, transformasi pendidikan dapat terwujud.SMP Negeri 3 Satu Atap Kedungjati terus berkomitmen memberikan layanan pendidikan terbaik, dengan semangat perubahan yang inklusif dan berkelanjutan. Upaya ini tercermin dalam capaian positif Rapor Pendidikan Tahun 2025, sebagai bukti nyata bahwa pendidikan berkualitas dapat dicapai melalui kerja keras, kolaborasi, dan fokus pada kebutuhan murid, pelatihan skill pada guru, budaya refleksi dan kolaborasi, merancang program peningkatan mutu yang tepat sasaran, mengedepankan kepemimpinan transformatif. Kata kunci: Transformasi pendidikan,Kurikulum Merdeka, kualitas pembelajaran, kepala sekolah, kompetensi guru.